ASSOCIATION OF AGE WITH GLEASON GRADE IN PATIENTS OF LOCALIZED PROSTATE CANCER (The Research of Medical Science Review, 2025)
OBJECTIVE: To look for association of age and other clinical factors with Gleason grade in patients of localized prostate cancer STUDY DESIGN: Cross-sectional Study SETTING AND DURATION: Medical Oncology Department, Combined Military Hospital Rawalpindi (CMH). December 2021 to December 2023 METHODOLOGY: This study was conducted on 140 male patients of newly diagnosed localized prostate cancer. All the patients underwent biopsy of prostate by standard protocol which was assessed by a consultant histopathologist. Gleason score as well as Gleason grade was assigned by the pathologist on the report. Age of the patient was ascertained by checking from national identity card. Clinical parameters other than age were recorded from clinical charts of the patients. RESULTS: A total of 140 male patients with localized prostate cancer were recruited for this analysis. Mean age of the patients we included in this study was 66.27±6.08 years. Out of total patients studied, 58 (41.4%) had Gleason Grade-I, 16 (11.4%) had Gleason grade-II, 29 (20.7%) had Gleason grade-III, 17 (12.1%) had Gleason grade-IV while 20 (14.3%) patients had Gleason Grade-V. Statistical analysis revealed that advancing age had statistically significant association with high Gleason grade in our study participants (pvalue<0.001). CONCLUSION: Patients of prostate cancer included in our study had Gleason grades I to V. Increasing age was found to be associated with high Gleason grade in patients of localized prostate cancer recruited in this study.